2010
DOI: 10.1038/cdd.2010.12
|View full text |Cite
|
Sign up to set email alerts
|

An essential function for the centrosomal protein NEDD1 in zebrafish development

Abstract: The centrosome is the primary microtubule organising centre of the cell. It is composed of many proteins, some of which make up the core of the centrosome, whereas others are used for specific functions. Although the cellular roles of many centrosomal proteins are well defined, much less is known about their functions and the role of the centrosome in development. In this study we investigated the function of NEDD1, a critical component of the centrosome essential for microtubule nucleation, in zebrafish (Dani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…4A,B ). We next assessed the localization of Nedd1 that is essential for γ-tubulin recruitment to the centrosome 54 55 56 . Endogenous Nedd1 colocalized with γ-tubulin at the basal body in GRP cells ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A,B ). We next assessed the localization of Nedd1 that is essential for γ-tubulin recruitment to the centrosome 54 55 56 . Endogenous Nedd1 colocalized with γ-tubulin at the basal body in GRP cells ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins have been suggested to play roles in γ-tubulin recruitment to the centrosome, but these effects may be species and/or cell type dependent. For example, Nedd1 was originally shown to be necessary for γ-tubulin localization to centrosomes in human cancer cell lines but was not required for centrosomal γ-tubulin recruitment in Xenopus laevis or Drosophila melanogaster ( Liu and Wiese, 2008 ; Zeng et al, 2009 ; Manning et al, 2010a ; Reschen et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, Nedd1 is essential for recruiting γ-tubulin to centrosomes (Haren et al, 2006; Lüders et al, 2006), and this is also the case in Zebrafish (Manning et al, 2010). Previous studies in Drosophila have indicated that γ-tubulin recruitment to centrosomes is partially disrupted when Dgp71WD is depleted from S2 cells or in brain cells from the original Dgp71WD GE30807 mutant (Dobbelaere et al, 2008; Verollet et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Dgp71WD and its human homologue Nedd1 are structurally unrelated to the γ-TuSC/γ-TuRC proteins, as they lack the conserved ‘Grip’ motifs found in these proteins (Gunawardane et al, 2003). In human cells and in Zebrafish, Nedd1/GCP-WD is essential for targeting the γ-TuRC to the centrosome (Haren et al, 2006; Lüders et al, 2006; Manning et al, 2010), and in human cells it also appears to have a role in centriole duplication (Haren et al, 2006). Nedd1 is also required to target the γ-TuRC to the spindle in human cells (Lüders et al, 2006), where it is thought to link the γ-TuRC to the Augmin complex, thus promoting MT nucleation within the spindle (Johmura et al, 2011; Uehara et al, 2009; Zhu et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%